Implementation of Coding Theory with The Extended Hamming Code in Steganography - Jannah, Nurul; Hamid, Nur (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2023)
Data security needs to be considered to avoid noise when sending data or data breaches by hackers. In this article, we implement data security using a combination of coding theory and steganography. The code used is an extended Hamming code [8.4]. The media used is a grayscale image of size of lengths 50,100,150,200,250 and 300 characters with 6 attempts. In addition, we show the PSNR result obtained and also the computation time.